Polymorphisms in maternal folate pathway genes interact with arsenic in drinking water to influence risk of myelomeningocele. Issue 9 (6th August 2015) - Mazumdar, Maitreyi; Valeri, Linda; Rodrigues, Ema G.; Ibne Hasan, Md Omar Sharif; Hamid, Rezina; Paul, Ligi; Selhub, Jacob; Silva, Fareesa; Mostofa, Md Golam; Quamruzzaman, Quazi; Rahman, Mahmuder; Christiani, David C.
<x xml:space="preserve">Abstract</x> BACKGROUND Arsenic induces neural tube defects in many animal models. Additionally, studies have shown that mice with specific genetic defects in folate metabolism and transport are more susceptible to arsenic‐induced neural tube defects. We sought to determine whether 14 single‐nucleotide polymorphisms in genes involved in folate metabolism modified the effect of exposure to drinking water contaminated with inorganic arsenic and posterior neural tube defect (myelomeningocele) risk. METHODS Fifty‐four mothers of children with myelomeningocele and 55 controls were enrolled through clinical sites in rural Bangladesh in a case–control study of the association between environmental arsenic exposure and risk of myelomeningocele. We assessed participants for level of myelomeningocele, administered questionnaires, conducted biological and environmental sample collection, and performed genotyping. Inductively coupled plasma mass spectrometry was used to measure inorganic arsenic concentration in drinking water. Candidate single‐nucleotide polymorphisms were identified through review of the literature. RESULTS Drinking water inorganic arsenic concentration was associated with increased risk of myelomeningocele for participants with 4 of the 14 studied single‐nucleotide polymorphisms in genes involved in folate metabolism: the AA/AG genotype of rs2236225 (MTHFD1), the GG genotype of rs1051266 (SLC19A1), the TT genotype of rs7560488 (DNMT3A), and the GG genotype of rs3740393 (AS3MT) with adjusted odds ratio of 1.13, 1.31, 1.20, and 1.25 for rs2236225, rs1051266, rs7560488, and rs3740393, respectively. CONCLUSION Our results support the hypothesis that environmental arsenic exposure increases the risk of myelomeningocele by means of interaction with folate metabolic pathways. Birth Defects Research (Part A) 103:754–762, 2015. © 2015 Wiley Periodicals, Inc.